2003
DOI: 10.1145/885651.781055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of LAS scheduling for job size distributions with high variance

Abstract: Recent studies of Internet traffic have shown that flow size distributions often exhibit a high variability property in the sense that most of the flows are short and more than half of the total load is constituted by a small percentage of the largest flows. In the light of this observation, it is interesting to revisit scheduling policies that are known to favor small jobs in order to quantify the benefit for small and the penalty for large jobs. Among all scheduling policies that do not require knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…A similar behavior is not observed in Fig. 13 since the burst losses are independent of the burst size for the flows destined to D 17 -D 20 .…”
Section: Ftp-type Long-lived Tcp Flowssupporting
confidence: 71%
See 2 more Smart Citations
“…A similar behavior is not observed in Fig. 13 since the burst losses are independent of the burst size for the flows destined to D 17 -D 20 .…”
Section: Ftp-type Long-lived Tcp Flowssupporting
confidence: 71%
“…We observe that for both destinations the average goodputs increase with the number of burstifiers. It is also observed that the average burst size increases linearly with the assembly timeout for flows destined to D 17 -D 20 . On the other hand, the average burst size first increases and then saturates for the flows destined to D 1 -D 4 .…”
Section: Ftp-type Long-lived Tcp Flowsmentioning
confidence: 85%
See 1 more Smart Citation
“…While such information is typically available in web servers, it is usually nearly impossible to obtain in Internet routers. An alternative strategy which has therefore been advocated for scheduling data flows is the Least Attained Service first (LAS) discipline also known as ForegroundBackground Processor Sharing (FBPS) [22,27,29,30]. In case the service requirement distribution has a decreasing failure rate, it has been shown that LAS stochastically minimizes the number of jobs in the system among all strategies that use no knowledge of the remaining job sizes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Foreground-Background (FB) [26], Least Attained Service (LAS) [27], Resource Allocation Queueing Fairness Measure (RAQFM) [28], and the Fair Sojourn Protocol (FSP) [11]. FB and LAS approximate the effectiveness of SRPT, without the need to know job sizes in advance.…”
Section: A Scheduling Policiesmentioning
confidence: 99%